GLYCEMIC INDEX OF INDIAN FLAT BREADS (CHAPATI) - M. SARADA DEVI, AMTUL MATEEN SHIREEN, V. VIJAYA LAKSHMI S. SUCHARITHA DEVI and (The Journal of Research, PJTSAU, 2017)
The study was undertaken to measure glycemic index of breakfast, chapati made of whole wheat flour (W1) and commercial multigrain flour (C1)and multigrain flour (D1) obtained from the production unit of Department of Foods and Nutrition, College of Home Science, Saifabad, Hyderabad, Blood glucose levels were measured by using â€œOne Touch Select Simpleâ€ Glucometer using finger prick method under fasting condition and at 30, 60, 90 and 120 minutes after consumption of the reference food (50 gglucose) and the test food (chapati made of W1, C1 and D1 each providing 50 g CHO). The glycemic index of chapati made of W1 was 54.9, C1 was 53.72 and D1 was 49.7. W 1, C1 and D1 chapati elicited lower glycemic response. Low glycemic index foods are defined as having a glycemic index of 55 or less. The incremental area under the blood glucoseresponse curves (IAUC) to test and reference foods were calculated geometrically using the trapezoid rule. The peak rise and glycemic response of C1 was higher than that of D1 and lower than W1. Thesedifferences could be due to the varied gluten contentÂ  of wheat having shown to influence the glycemic index of chapati.